The Light of Egypt; Or, The Science of the Soul and the Stars $1 (BVolume 2s - Burgoyne, Thomas H.; Wagner, Belle M. (Salt Lake City, UT : Project Gutenberg, 1999)
"The Light of Egypt; Or, The Science of the Soul and the Stars $1 (BVolume 2" by Thomas H. Burgoyne is a scientific publication written in the early 20th century, particularly around the turn of the century. The work delves into subjects of astrology, occultism, and esoteric knowledge, aiming to illuminate the connections between celestial phenomena and the human experience. It presents itself as a guide for spiritual seekers and occult students, asserting that a thorough understanding of the universe's laws can lead to greater self-awareness and enlightenment. The opening of the text introduces readers to the overarching themes of astrology and its significance. It emphasizes the importance of the Zodiac, the constellations, and their metaphysical implications on human life and development. Burgoyne expresses that the celestial influences shape not only individual destinies but also larger cycles affecting humanity as a whole. The chapter outlines the nature of astrology as a divine language through which one can decipher spiritual truths, encouraging readers to embrace this study as a means to grasp deeper existential concepts and elevate their spiritual understanding. The text sets the groundwork for exploring these profound ideas in subsequent chapters, promising insights into the mysteries of the soul and its journey through various phases of existence. (This is an automatically generated summary.)s
Release date is 1999-02-01
Keywords: Occultism; Astrology